Effect of Intermolecular Interactions on Metal‐to‐Metal Charge Transfer: A Combined Experimental and Theoretical Investigation - Jiao, Cheng‐Qi; Meng, Yin‐Shan; Yu, Yang; Jiang, Wen‐Jing; Wen, Wen; Oshio, Hiroki; Luo, Yi; Duan, Chun‐Ying; Liu, Tao (Angewandte Chemie International Edition, 2019)
Understanding the effects of intermolecular interactions on metal‐to‐metal charge transfer (MMCT) is crucial to develop molecular devices by grafting MMCT‐based molecular arrays. Herein, we report a series of solvent‐free Fe2Co2 compounds sharing the same cationic tetranuclear {[Fe(PzTp)(CN)3]2[Co(dpq)2]2}2+ (PzTp−=tetrakis(pyrazolyl)borate, dpq=dipyrido[3,2‐d:2′,3′‐f]quinoxaline) square units but having anions with different size, including BF4−, PF6−, OTf−, and [Fe(PzTp)(CN)3]−. Intermolecular π⋅⋅⋅π interactions between dpq ligands, which coordinate to cobalt ions in the {[Fe(PzTp)(CN)3]2[Co(dpq)2]2}2+ units, can be modulated by introducing different counterions, regulating the distortion of the CoN6 octahedron and ligand field around the cobalt ions. This change results in different MMCT behavior. Computational analyzes reveal the substantial role of the intermolecular interactions tuned by the presence of different counteranions on the MMCT behavior. Transfer window: A series of solvent‐free {[Fe(PzTp)(CN)3]2[Co(dpq)2]2}⋅2 A− compounds were synthesized. The variation in π⋅⋅⋅π interactions between dpq ligands coordinated to Co centers can alter the distortion of the CoN6 octahedron and ligand field around the Co ions, thereby allowing control of the thermally and photo‐induced metal‐to‐metal charge transfer (MMCT).